Evidence, Persuasion and Diversity - Allen, Derek (Informal Logic, 2020)
My topic is the theme of the E-OSSA 12 conference, namely Evidence, Persuasion and Diversity. I will present relevant material from a selection of Canadian legal cases, along with background information as needed and commentary. My primary focus will be on two landmark Supreme Court of Canada cases—an Aboriginal law case and a case that was both a constitutional law case and a criminal law case.